Yellow fever in Africa and the Americas: a historical and epidemiological perspective - Jean-Philippe Chippaux; Alain Chippaux (Journal of Venomous Animals and Toxins including Tropical Diseases, 2018)
Abstract Yellow fever was transported during the slave trade in the 15th and 16th centuries from Africa to the Americas where the virus encountered favorable ecological conditions that allowed creation of a sustainable sylvatic cycle. Despite effective vector control and immunization programs for nearly a century, yellow fever epidemics reemerged in many Latin American countries, particularly Brazil. The emergence or reemergence of vector-borne diseases encompasses many intricate factors. Yellow fever outbreaks occur if at least three conditions are fulfilled: the introduction of the virus into a non-immune human community, presence of competent and anthropophilic vectors and insufficiency of prevention and/or adequate management of the growing outbreak. On the other hand, two weapons are available to constrain yellow fever: vector control and immunization. In contrast, yellow fever is absent from Asia and the Pacific despite the presence of the vector and the susceptibility of human populations to the virus. Based on a review of the global history of yellow fever and its epidemiology, the authors deliver some recommendations for improving the prevention of epidemics.